Asymmetry of face in light of measured curvatures tragion-nasion tragion-subnasale and tragion-gnathion - Malinowski, Andrzej; Losiak, Barbara (Anthropological Review, 1974)
The results of investigated facial curvatures: tragion-nasion, tragion-subnasale and tragion-gnathion in boys and girls at the age from 7 to 15, and 19 have been presented. Data concerning frequency of occurence of symmetry and asymmetry have been set together in table 1, in tables 2, 3, 4, on the other hand details of mean values of boys’ and girls’ measurements in their age groups. It was found that with age the frequency of occurrence of asymmetric faces somewhat increases. A left-sided asymmetry occurs more often and manifests itself in higher values of measurements.